An Analysis of Health Benefits of Guava (International Journal of Innovative Research in Engineering & Management, 2023)
Guava is a tropical fruit native to South  America. It belongs to the Myrtaceae family and is a  well-liked plant. In contrast to other fruits, guava is  untreated with chemicals, making it a healthier option. It  has long been used as a homoeopathic herb to treat a  variety of ailments throughout the globe. Oleanolic acid,  tannins, quercetin, ursolic acid, triterpenes, pentacyclic  triterpenoid, saponins, carotenoids, amritoside, guajanoic  acid, lectins, leucocyanidin, beta-sitosterol and uvaol are  among the active components. Guava contains  antibacterial, anti-malarial, anti-diarrheal, anti inflammatory, anti-cancer, anti-hyperglycemic, and  antioxidant properties, among others. Several studies  have revealed that guava contains a number of  pharmacological active components that are responsible  for a variety of biochemical activities, including  antidiabetic, antimicrobial, antidiarrheal, anti-oxidant,  anti-pyretic, cardioactive, hepatoprotective,  immunomodulatory, spasmolytic, and contractile effects,  which are discussed further in the review. This article  discusses about pharmacological activities and how they  may be used to treat a variety of illnesses and diseases.
Keywords: Fruit; Guava; Health; Myrtaceae; Vitamin